Teaching with AI: A Practical Guide to a New Era of Human Learning - Adhikari, Eka Raj (Journal of Technical and Vocational Education and Training, 2025)
Teaching with AI: A Practical Guide to a New Era of Human Learning, authored by Jose Antonio Bowen and C. Edward Watson, Baltimore, Johns Hopkins University Press, 2024, pp. 270. Paperback & E-book: 24.95. ISBN: 978-1-4214-4922-7 (Paperback), ISBN: 978-1-4214-4923-4 (E-book)